Formation of duty behavior with consideration of the presence of the non-governmental economy - Kuzmynchuk, Nataliia; Nazarova, Tetiana; Drugova, Olena; Vyadrova, N. G; Chkheailo, Anna (Університет банківської справи, 2019)
In this study, the main attention is paid to the problem of "shadowing" the Ukrainian economy during the crisis period. Theoretical approaches to determining the functions of taxes and factors affecting real tax revenues were studied. A scientific study was carried out that will reveal the motives of the behavior of taxpayers, who are explicitly or implicitly laid in the basis of approaches to the formation of the mechanism of taxation and tax policy of the state. Consequently, we tried to determine motives of the behavior of taxpayers, which explicitly or implicitly form the basis of approaches to the formation of the tax mechanism and the tax policy of the state. So, we tried to determine the level of the shadow economy, taking into account the modeling of the dynamics of tax behavior of economic entities, which, of course, will allow to increase the efficiency of management of the budget process, in particular, planning of budget expenditures to regional authorities. The article defines the necessity of improving the tools of state regulation of the economy, taking into account the specific conditions of development, and creates scientific and methodological support for the formation of concepts, strategies and programs of socio-economic development of the country and regions by the authorities. The theoretical positions concerning the role of the state in the regulation of fiscal-budgetary relations in the light of the evolution of the views of the known economic schools are outlined, and the expediency of introducing the views of well-known economic schools into practice has been outlined, which will help to develop regulatory measures to overcome negative phenomena in the economy It is generally agreed that evasion of payment of taxes and fees leads to a number of negative consequences for both state power, and for the country's society (the threat of development, the collapse of the national economy, the negative influence on the distribution of resources redistribution between the spheres of economy, the threat to democratic values and social institutions). Systematically conceptualized the motives of the behavior of the subtitles, which were used as the basis for the formation of the mechanism of the podcasting and subjective policy of the state. Factors influencing the regulatory policy of the country and the factors influencing the adoption of decisions by the parties associated with the subtraction of subtractions are considered. The structure of the mechanization of the formation of a subtle behavior is proposed. The problems of tax evasion were identified and countermeasures were proposed to facilitate the development of an effective state anti-political policy in Ukraine.

Основну увагу приділено проблемі "тінізації" економіки України в кризовий період. Вивчено теоретичні підходи до визначення функцій податків і факторів, що впливають на реальні податкові надходження. Проведено наукове дослідження, яке дозволить виявити мотиви поведінки платників податків, які явно або неявно закладаються в основу підходів до формування механізму оподаткування і податкової політики держави. Отже, ми спробували визначити рівень тіньової економіки при врахуванні моделювання динаміки податкової поведінки економічних суб’єктів, що, безумовно, дозволить підвищити ефективність управління бюджетним процесом, зокрема планування бюджетних видатків регіональним органам влади. Визначено необхідність удосконалення інструментарію державного регулювання економіки, що ураховує конкретні умови розвитку і створює науково-методичне забезпечення формування органами влади концепцій, стратегій та програм соціально-економічного розвитку країни та регіонів. Окреслено теоретичні положення щодо ролі держави в регулюванні фінансово-бюджетних відносин у світлі еволюції поглядів відомих економічних шкіл, у результаті чого встановлено доцільність у впровадженні поглядів відомих економічних шкіл у практику, що допоможе виробити регулятивні заходи подолання негативних явищ в економіці. Обґрунтовано, що ухилення вiд сплaти подaткiв тa зборiв призводить до низки негaтивних нaслiдкiв як для держaвної влaди, тaк i для соцiуму крaїни (зaгрозa розвитку, зaгрозa нaцiонaльнiй економiцi, негaтивний вплив нa розподiл тa перерозподiл ресурсiв мiж сферaми економiки, зaгрозa демокрaтичним цiнностям тa соцiaльним iнститутaм). Системaтизовaно концепцiї про мотиви поведiнки плaтникiв подaткiв, якi поклaдено в основу пiдходiв до формувaння мехaнiзму оподaтковувaння тa подaткової полiтики держaви. Розглянуто фaктори впливу нa регуляторну полiтику крaїни та фaктори, якi впливaють нa ухвалення плaтникaми рiшень, пов'язaних зi сплaтою подaткiв. Запропоновано структуру мехaнiзму формувaння подaткової поведiнки. Виявлено проблеми ухилення від сплати податків та запропоновано механізми протидії з метою сприяння розробленню ефективної державної антитіньової політики в Україні.
Формувaння подaткової поведiнки з урaхувaнням нaявностi тiньової економіки
Keywords: tax behavior; taxpayers; motivation of taxpayers; tax revenues; shadoing economy; economization of the economy; подaткова поведiнка; платники податків; мотивація платників податків; податкові надходження; тіньова економіка; детiнiзaцiя економiки